Human papillomavirus infection affects the immune microenvironment and antigen presentation in penile cancer - Guimarães, Sulayne Janayna Araujo; Vale, André Alvares Marques; Rocha, Mirtes Castelo Branco; Butarelli, Ana Luiza de Araújo; da Silva, Jenilson Mota; Deus, Amanda Jordão Silva de; Nogueira, Leudivan; Coelho, Ronald Wagner Pereira; Pereira, Silma Regina; Azevedo-Santos, Ana Paula Silva (Frontiers in Oncology, 2024)
Penile squamous cell carcinoma (PSCC) is a largely neglected condition, predominantly affecting underdeveloped regions, and is associated with risk factors such as low socioeconomic status, phimosis, and human papillomavirus (HPV) infection. Unlike other urogenital cancers, its pathophysiology and therapeutic targets remain poorly understood, particularly regarding the immune response to the tumor microenvironment. This study aims to investigate immune cell infiltration profiles, dendritic cell maturation, and lymphocyte apoptosis in both HPV-positive and HPV-negative PSCC. Clinical and histopathological data, along with peripheral blood and tumor tissue samples, were collected from 30 patients (66.6% were HPV-positive and 33.3% HPV-negative), with an additional 19 healthy donors serving as controls. Tumor-infiltrating immune cells were analyzed following enzymatic digestion of tumor tissue, enabling detailed phenotypic characterization. A simulated tumor microenvironment was created using supernatants derived from primary cultures of HPV-positive PSCC tumors. Peripheral blood mononuclear cells were isolated and differentiated into dendritic cells (Mo-DCs) for further phenotyping and lymphoproliferation assays. Lymphocytes from healthy donors and patients were exposed to tumor culture supernatants to evaluate apoptosis induced by the tumor microenvironment. Results showed that HPV-positive tumors exhibited lower T lymphocyte frequencies compared to HPV-negative tumors. Additionally, patients infected with high-risk HPV demonstrated reduced maturation rates of Mo-DCs and decreased expression of co-stimulatory molecules on these cells compared to healthy donors. Furthermore, Mo-DCs from hrHPV-positive patients showed impaired lymphoproliferation capacity relative to controls, while HPV-negative patients exhibited a trend towards reduced lymphoproliferative ability. Regarding the simulated tumor microenvironment, lymphocytes from healthy donors underwent apoptosis, contrasting with patients' lymphocytes, which showed increased viability when cultured with tumor supernatants. These results underscore the impact of HPV infection on T lymphocyte infiltration, Mo-DC maturation, and lymphocyte survival in PSCC, offering critical insights for advancing our understanding of the tumor microenvironment and guiding the development of immunotherapy strategies.